Mechanics of the Jump Shot: The “Dip” Increases the Accuracy of Elite Basketball Shooters - Penner, Luke S. J. (Frontiers in Psychology, 2021)
The present study assessed the mechanics of the basketball jump shot to determine whether or not the “dip” increased shot accuracy. There remained a debate between coaches who believed “dipping” was too slow and coaches who believed “dipping” increased accuracy. A mixed design was used for the present study with elite high-school and university players all performing shots with and without the “dip” at four distances: the last hash mark before the free throw line (3.125 m), the length of an imaginary hash mark beyond the free throw line (4.925 m), the top of the free throw circle (6.025 m), and the three-point line (6.750 m). These distances best emulated where the majority of shots were attempted in a game. Thirty-six athletes completed the study, with accuracy and shot quality being measured using Hardy-Parfitt’s six-point scale. The results of the present study indicated that the “dip” led to approximately a 7–9% increase in accuracy of the jump shot for both high school shooters, and university shooters, suggesting that coaches should begin to teach the “dip” in a player’s shooting motion to improve scoring results.